Restore me - Mafi, Tahereh (Mafi, Tahereh. Shatter me series, 2018)
"It's been sixteen days since Juliette Ferrars killed the supreme commander of North America and took over as ruler of the Reestablishment on the continent ... Juliette thought she'd won. She took over sector 45 and now has Warner by her side. But she's still the girl with the ability to kill with a single touch--and with so much power in her young hands, the world is watching her every move, waiting to see what happens next."--Jacket.